Biological Additives and Platelet Concentrates for Tissue Engineering on Regenerative Dentistry: Basic Science and Concise Review - Yanmin, Zhou (Asian Journal of Pharmaceutics (AJP), 2017)
In oral surgery, there is an increased concern for soft and hard tissue wound healing processes, and the development of bioactive additives for targeted surgical sites has become an important challenge in the past three decades. Recently, platelet concentrates (PCs) have been identified as satisfactory bioactive materials that increase the speed of the healing process in peri-implant surgical sites. Moreover, recent convincing results in several clinical studies and literature reviews have demonstrated the importance of these bioactive materials in the stimulation of the healing process and have provided promising results for the use in the future. To stimulate and ensure the healing for both soft and hard tissues in the oral region, there is convincing evidence that PCs can serve as an autologous source of growth factors and healing cytokine biomolecules, such as platelet-rich plasma, platelet-poor plasma, and platelet-rich fibrin (PRF) release, which plays a crucial role in promoting hemostasis and the wound healing process. In the recent studies, the primary concern has been the PCs in general, and particularly, PRF. The following review attempts to discuss the current data for researchers and clinicians to understand the value of combining biological additives with platelet-derived products for the healing of surgical sites. This approach is of particular concern, as the critical processes and effect on the speed of action are a controversial topic for both researchers and clinicians alike.